Influence of Concrete Sludge Addition in the Properties of Alkali-Activated and Non-Alkali-Activated Fly Ash-Based Mortars - Fotini Kesikidou; Stavroula Konopisi; Eleftherios K. Anastasiou (Advances in Civil Engineering)
This study investigated the use of concrete sludge, a by-product of the ready-mix concrete industry, in combination with high-calcium fly ash in binary cementless binders. Concrete sludge was used in substitution rates ranging from 0% to 60% in test fly ash-based mortars to determine potential synergy. The mortars were tested for fresh and hardened properties; workability, viscosity, strength development, open porosity, early-age shrinkage, and analytical tests were carried out. A mortar with 50% fly ash and 50% limestone filler as binders was used for comparison purposes. Furthermore, a series of mortars with fly ash and concrete sludge were alkali-activated in order to determine potential strength gain. In the activated mortars, two fractions of concrete sludge were used, under 75 μm and 200 μm, due to different silicon oxide contents, while one mortar was cured at 40°C to investigate the effect of heating on alkali activation. Results show that sludge contributes to the formation of C-S-H and strength development when used in combination with high-calcium fly ash even at high replacement rates. The alkali activation of fly ash-concrete sludge system contributed to early-age strength development and to early-age shrinkage reduction.